Risky Behaviors of University Students: A Cross-Sectional Study - Hilal Ozcebe; Sarp Uner; Sabahat Tezcan; Nuket Paksoy Erbaydar; Gokhan Teletar (Turkish Society of Public Health Specialists, 2012)
Objective: This study aimed to identify certain risky behavior patterns (unsafe sex, tobacco and drug use, and binge drinking) and the factors affecting these behaviors among first- and third-year students in a university. Method: The study included a total of 8407 students enrolled as first- (4392) and third- (4015) year students. A self-administered questionnaire was used for data collection. In data analysis, respecting sampling weights, models were formed by logistic regression method to determine factors that affect the risky behaviors. Results: 731 male-1114 female students from the first year and 560 male-1096 female students from the third year were interviewed. Male students were found to be engaged in risky behaviors more frequently than females. Logistic models of the study indicated that gender, place of residence, relationship with parents, and socialization with friends have profound effects on risky behaviors. Conclusion: After leaving home, young people develop their own lifestyles, and this study demonstrates that lifestyle is the main effective factor for risky behaviors in this group. Universities need to assume more responsibility to guide students' lives and to provide the facilities and opportunities that encourage and facilitate their adoption of a healthy lifestyle.   Key Words: University students, risky behaviours Bir Üniversitede Öğrencilerin Riskli Davranışları: Kesitsel Bir Çalışma Amaç: Bu çalışmanın amacı, bir üniversitenin birinci ve üçüncü sınıf öğrencileri arasında bazı riskli davranış modellerini (güvensiz seks, tütün ve uyuşturucu kullanımı ve aşırı alkol) ve bu davranışları etkileyen faktörleri saptamaktır. Yöntem: Araştırmanın evrenini birinci (4392) ve üçüncü (4015) sınıflarda kayıtlı 8407 öğrenci oluşturmaktadır. Veri öğrencilerin gözlem altında doldurdukları anket aracılığı ile toplanmıştır. Riskli davranışları etkileyen faktörleri belirlemek için lojistik regresyon yöntemi modellemesi kullanılmıştır. Bütün istatistiksel analizlerde ağırlıklı yüzdeler dikkate alınmış ve kullanılmıştır. Bulgular: Çalışmada birinci sınıflardan 731 erkek-1114 kadın ve üçüncü sınıflardan 560 erkek-1096 kadın öğrenci yer almıştır. Araştırmada erkek öğrencilerin kadınlara göre daha fazla riskli davranışlarda bulunduğu saptanmıştır. Çalışma verilerinin lojistik regresyon modellemesinde cinsiyet, aile ile ilişkiler, arkadaşlar ile sosyalleşme ve yaşam koşulları ile öğrencilerin riskli davranışları ile anlamlı düzeyde ilişkili olduğu saptanmıştır. Sonuç: Evden ayrıldıktan sonra, genç insanlar kendi yaşam tarzlarını geliştirmektedir. Bu çalışma bu grupta yaşam tarzının riskli davranışları etkileyen temel bir faktör olduğunu göstermektedir. Gençlerin yaşamlarına rehberlik etmek ve sağlıklı yaşam tarzını geliştirici ve benimsenmesini kolaylaştırıcı olanakların ve fırsatların sağlanması için üniversitelerin daha fazla sorumluluk üstlenmesi gerekmektedir. Anahtar Kelimeler: Üniversite öğrencileri, riskli davranışlar